Preliminary Screening Questionnaire for Sjögren's Syndrome in the Rheumatology Setting. Issue 2 (14th March 2022) - Yu, Kimberley; Ying, Gui-Shuang; Vivino, Frederick B.; Gonzales, John A.; Massaro-Giordano, Mina; Bunya, Vatinee Y.
Abstract : Objective: Sjögren's syndrome (SS) is frequently undetected or misdiagnosed as other rheumatologic diseases. We aimed to develop an SS screening questionnaire for the rheumatology practice. Methods: We developed the Sjögren's Syndrome Screening Questionnaire (SSSQ) via secondary analysis of data from 974 participants referred by rheumatologists to the Sjögren's International Collaborative Clinical Alliance (SICCA) study. Participants answered 88 questions regarding symptoms, medical history, and demographics. They underwent ocular, dental, and serologic tests and were classified as SS or non-SS using the 2016 American College of Rheumatology/European League Against Rheumatism classification criteria. We conducted univariate and multivariate logistic regression to identify questions most discriminative of SS, from which we derived an individual's likelihood of SS ("SSSQ score"). Results: Five questions were significantly discriminative of SS in the multivariate analysis ( p < 0.05): (1) Can you eat a cracker without drinking a fluid/liquid? (no: odds ratio [OR], 1.39; 95% confidence interval [CI], 1.06–1.82]); (2) How would you describe your dental and oral health in general? (fair/poor: OR, 1.68; 95% CI, 1.04–2.75); (3) During the last week, have you experienced tearing? (none of the time: OR, 2.26; 95% CI, 1.23–4.34); (4) Are you able to produce tears? (no: OR, 1.62; 95% CI, 1.12–2.37); and (5) Do you currently smoke cigarettes? (no: OR, 2.83; 95% CI, 1.69–4.91). SSSQ score ≥7 (possible range, 0–11) distinguishes SS from non-SS patients with 64% sensitivity and 58% specificity (area under receiver operating characteristic curve, 0.65). Conclusions: The SSSQ is a simple 5-item questionnaire designed to screen for SS in clinical practice, with a potential impact to reduce delays in diagnosis.